Minor Postoperative Increases of Creatinine Are Associated With Higher Mortality and Longer Hospital Length of Stay in Surgical Patients. Issue 4 (August 2016) - Kork, Felix; Balzer, Felix; Spies, Claudia D.; Wernecke, Klaus-Dieter; Ginde, Adit A.; Jankowski, Joachim; Eltzschig, Holger K.
Abstract : (Abstracted from Anesthesiology, 123:1301–1311, 2015) In this single-center retrospective cohort study, the authors examined the impact of acute kidney injury (AKI) and minor kidney function impairment on in-hospital morbidity, mortality, and hospital length of stay (HLOS) in a broad population of surgical patients. The authors measured baseline and postoperative creatinine levels, a marker of subclinical postoperative kidney dysfunction, and hypothesized that even minor increases in levels could lead to adverse outcomes.